2013
DOI: 10.1021/ja409781c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biologically Active N- and O-Linked Glycans with Multisialylated Poly-N-acetyllactosamine Extensions Using P. damsela α2-6 Sialyltransferase

Abstract: Sialosides on N- and O-linked glycoproteins play a fundamental role in many biological processes and synthetic glycan probes have proven to be valuable tools for elucidating these functions. Though sialic acids are typically found α2-3 or α2-6-linked to a terminal non-reducing end galactose, poly-LacNAc extended core-3 O-linked glycans isolated from rat salivary glands and human colonic mucins have been reported to contain multiple internal Neu5Acα2-6Gal epitopes. Here, we have developed an efficient approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 27 publications
3
58
0
Order By: Relevance
“…Analogues 3k and 3l are multisialylated di-LacNAc products, which were prepared with bacterial sialyl-transferase. 3334 Notably, the N-glycans are derived from a natural glycan isolated from eggs, ( SGP , Figure 3A) which is attached to asparagine, facilitating subsequent conjugation strategies. 35 …”
Section: Resultsmentioning
confidence: 99%
“…Analogues 3k and 3l are multisialylated di-LacNAc products, which were prepared with bacterial sialyl-transferase. 3334 Notably, the N-glycans are derived from a natural glycan isolated from eggs, ( SGP , Figure 3A) which is attached to asparagine, facilitating subsequent conjugation strategies. 35 …”
Section: Resultsmentioning
confidence: 99%
“…For example, by Danishefsky 7a, 15 constructed a core pentasaccharide by glycosylating a trisaccharide with a monosaccharide thioether donor; Unverzagt 16 synthesized multi-antennary complex type N-glycans with acetated Schmidt’s trichloroacetimidate donor; Wong 8a used oligosaccharyl fluorides as donors to produce bi-, tri- and tetra-antennary complex type N-glycans; Boons 9 developed a strategy by sequential removal of the protecting groups, and then by chemical glycosylation using a diverse set of trifluoroacetimidate donors. In these cases, to prepare various glycosyl donors, a temporary anomeric protecting group was used and then transformed into trichloroacetimidates, fluorides or trifluoroacetimidates, depending on the choice of glycosylation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…6 Among chemically synthesized N-glycans, only few contains terminal sialic acid (Sia) due to difficulties in sialic acid chemistry, 7 which was later overcome by enzymatic glycosylation using sialyltransferases. 8 Most recently, Boons developed a strategy for chemoenzymatic synthesis of asymmetrical N-glycans, and 14 tri-antennary complex N-glycans were obtained. 9 Nevertheless, only a few N-glycan structures were prepared in each report, mainly due to their complexity and diversity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many studies, glycosylation has been shown to affect the viral attachment or penetration steps via the modification of cellular receptors or viral envelope glycoproteins. For instance, the O-linked glycoproteins of ␣2,3-or ␣2,6-linked sialic acids were shown to play important roles during infection by IAV and other viruses, including the coxsackievirus A24 variant and enterovirus 70 (42)(43)(44)(45). Furthermore, the envelope proteins of many viruses, such as human immunodeficiency virus type 1, HCV, Ebola virus, and herpes simplex virus 1, have been shown to be modified by O-linked glycosylation, which influences the attachment of viral virions to the cell surface (42,(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%